Critical Thingking Ability In Islamic Education Through Kurikulum Merdeka Character Learning - Wildan Diniati, Siti; Yusfiq, Yusfiq Candra Afnibas; Al Mujahid, Usamah; Susilawati, Wati; Kariadinata, Rahayu kariadinata (Journal of Islamicate Studies, 2023)
Critical thinking skills in the 21st century is needed in Indonesia. In fact, students still need to improve critical thinking ability, especially in Islamic education learning. Using appropriate methods of learning based on the Kurikulum Merdeka is one way to develop critical thinking abilities. That is by using Problem Based Learning method and Project Based Learning Method in their learning activities. This study aims to know student's critical thinking abilities by learning with Kurikulum Merdeka's character with model learning based on gender. The method used quasi experiment through two-way ANOVA test. This study was conducted at a Junior High School in Majalengka, with a sample size of 63 students from three classes. Class VIII is made up of 21 students who are studying Islamic religious education utilizing the Project Based Learning model. The Problem Based Learning model was used by class VIII B (20 people), and the conventional model was used by class VIII C (22 people). The results show that there is the deffrences between student’s critical thinking ability based on learning model. 1) Problem Based Learning and Project Based Learning learning models affect the critical thinking skills of Majalengka Junior High School students. 2) Gender influences students' critical thinking skills. 3) Interaction between the learning model and gender factors in determining students' critical thinking abilities has no effect.